2009
DOI: 10.1021/es8028928
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disrupting Effects of Herbicides and Pentachlorophenol: In Vitro and in Vivo Evidence

Abstract: The potential for agricultural chemicals to cause endocrine disruption (ED) in humans and wildlife is an increasing concern; however, the effects of commonly used pesticides at environmentally relevant concentrations are largely unknown. Therefore, 12 environmentally relevant pesticides (11 herbicides and pentachlorophenol (PCP)) were tested for their endocrine disrupting potential in two in vitro assays. A recombinant yeast screen was used to detect receptor mediated (anti-) estrogenic and (anti-) androgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(101 citation statements)
references
References 36 publications
1
98
2
Order By: Relevance
“…with these steroid receptors were approximate equivalent. These results may provide molecular evidences for previously reported estrogenic, anti-estrogenic, anti-androgenic activity of PCP in vitro (Suzuki et al, 2001;Jung et al, 2004;Orton et al, 2009;Li et al, 2008aLi et al, , 2008bLi et al, , 2010b and in vivo (Zha et al, 2006;Zhang et al, 2008a). Moreover, molecular docking results showed that PCP could not interact with any of the agonistic or antagonistic conformations of CYPs.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…with these steroid receptors were approximate equivalent. These results may provide molecular evidences for previously reported estrogenic, anti-estrogenic, anti-androgenic activity of PCP in vitro (Suzuki et al, 2001;Jung et al, 2004;Orton et al, 2009;Li et al, 2008aLi et al, , 2008bLi et al, , 2010b and in vivo (Zha et al, 2006;Zhang et al, 2008a). Moreover, molecular docking results showed that PCP could not interact with any of the agonistic or antagonistic conformations of CYPs.…”
Section: Discussionsupporting
confidence: 75%
“…PCP has been demonstrated to display estrogenic, anti-estrogenic, antiandrogenic, thyroid receptor and retinoid X receptor antagonistic activity in vitro (Suzuki et al, 2001;Jung et al, 2004;Orton et al, 2009;Li et al, 2008aLi et al, , 2008bLi et al, , 2010b and disturb the hypothalamic-pituitary-gonadal (HPG) axis in vivo (Zha et al, 2006;Zhang et al, 2008a). However, the underlying mechanism such as molecular initiating event (MIE) and the following regulating process has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hormone receptor screening in vitro suggests a preponderance of anti androgenic activity compared with estrogenic activity in non organochlorine (currentuse) pesticides. For example, Kojima et al (2004) screened 161 pesticides and reported that 52 were anti androgenic, whereas only 29 were estrogenic, and Orton et al (2009) reported that 6 of 12 pesticides screened were anti androgenic and none were estrogenic. There is a good correlation between androgen receptor (AR) antagonist properties and in vivo anti androgenic effects, and there is also good evidence that androgen-sensitive end points are demasculinized in male rats when exposed in utero to a wide range of pesticides.…”
Section: Researchmentioning
confidence: 99%
“…Nowadays, PCP is a restricted use pesticide and is no longer available to the public due to its carcinogenic and endocrine disrupting effects [55,56]. Morales et al [40] studied the effect of PCP in the expression of heat-shock genes, concluding that, at a concentration of 1 µM, no significant effects were observed in the expression of HSP70 and HSC70.…”
Section: Butyl Benzyl Phthalatementioning
confidence: 99%